Grand Alumni Home Coming 2017 / Suzaina Ismail - Ismail, Suzaina (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
Grand Alumni Homecoming programme was organized by the Alumni Association of UiTM Perak Branch in collaboration with the Research, Industrial Link-ages, Community and Alumni Network Division. The main high-light was the Grand Alumni Homecoming Dinner which was at-tended by almost 500 UiTM Perak Branch alumni graduated from 1985 until 2017. The dinner was officiated by YB Dato' Nolee Ashilin Mohamed Radzi, the Committee Chairman of Perak Tour-ism, Arts, Culture, Communication and Multimedia. The other honorary guests were the Deputy Vice Chancellor (Student Af-fairs) of UiTM, Prof Dato' Dr Abdullah Mohamad Said and Datin Ir Dr Hajah Zainab Mohamed, the former Rector of UiTM Perak Branch. The guests were entertained by Danseni Tapah, Danseni Seri Iskandar and the guest artist, Amir Ukays.10 alumni icons from different categories were proudly an-nounced during the dinner including the icon for creative in-dustry, humanity, cultural, sports, innovation, professional, re-search, entrepreneurship, young alumni and personality. From these 10 icons, Mr Muhammad Hatta Dolmat was announced as the recipient for the Best of the Best Icon Award. The award for the most presence during the dinner was won by the Town and Regional Planning Department.